Evaluation of Traffic Performance on the Ciledug–Pabuaran Road Section on Cirebon Regency - Fauzan Adzim; Martinus Agus Sugiyanto (Publica Scientific Solution, 2026)
The growth of industrial areas in East Cirebon Regency has increased transportation activities and traffic volume on the Ciledug–Pabuaran Road, potentially reducing traffic performance. This study aims to evaluate traffic performance on the Ciledug–Pabuaran Road segment and analyze the impact of industrial development on traffic conditions. The research employed a quantitative approach using field surveys and descriptive analysis. Primary data were collected through traffic volume surveys, vehicle speed measurements, and roadside friction observations, while secondary data were obtained from relevant agencies and the Indonesian Highway Capacity Guidelines (PKJI). The analysis included calculations of traffic volume, road capacity, volume-to-capacity ratio (V/C Ratio), and Level of Service (LOS). The results indicate that the average traffic volume reached approximately 16,000 vehicles per day, while the effective road capacity was 1,078 vehicles per hour. The V/C ratio of 1.05 indicates that the road segment operates beyond its capacity (overcapacity). High roadside friction caused by industrial activities contributed to a decline in the Level of Service to categories D–E during peak hours. The study concludes that industrial area development has a significant impact on increasing traffic congestion and reducing road performance. Therefore, mitigation measures such as the implementation of Traffic Impact Analysis (ANDALALIN), industrial access management, and road capacity improvements are necessary to support traffic flow efficiency and road safety.